Barrett's esophagus: The pathomorphological and molecular genetic keystones of neoplastic progression. (6th December 2021) - Maslyonkina, Ksenia S.; Konyukova, Alexandra K.; Alexeeva, Darya Y.; Sinelnikov, Mikhail Y.; Mikhaleva, Liudmila M.
Abstract: Barrett's esophagus is a widespread chronically progressing disease of heterogeneous nature. A life threatening complication of this condition is neoplastic transformation, which is often overlooked due to lack of standardized approaches in diagnosis, preventative measures and treatment. In this essay, we aim to stratify existing data to show specific associations between neoplastic transformation and the underlying processes which predate cancerous transition. We discuss pathomorphological, genetic, epigenetic, molecular and immunohistochemical methods related to neoplasia detection on the basis of Barrett's esophagus. Our review sheds light on pathways of such neoplastic progression in the distal esophagus, providing valuable insight into progression assessment, preventative targets and treatment modalities. Our results suggest that molecular, genetic and epigenetic alterations in the esophagus arise earlier than cancerous transformation, meaning the discussed targets can help form preventative strategies in at‐risk patient groups. Abstract : Several important keystone genetic events occur during carcinogenesis in the distal esophagus. These processes should be diagnosed during routine evaluation of patients with Barrett's esophagus to prevent disease progression and malignization. The aforementioned genetic aberrations are detected as early as 2 years before diagnosis of esophageal carcinoma.